Privacy, security and resilience in mobile healthcare applications. Issue 3 (4th March 2023) - Lin, Wenjun; Xu, Ming; He, Jingyi; Zhang, Wenjun
ABSTRACT: With the advent of mobile applications in health service systems, concerns such as security, privacy, usability, and resilience have been raised. We developed a system view of the concepts of security, privacy, resilience along with their relationship, and proposed a set of principles for designing a mobile application linking the resilience and security in privacy protection. Such study was not found in literature before. This system's view of privacy, security, and resilience has laid a foundation to develop a more effective service system. A case study is presented to illustrate how the proposed principles work in a mobile healthcare application.